REGISTER PADA SPORTFISHING ANNOUNCER TALK DALAM PROGRAM “MANCING MANIA” TRANS7 - Farida Indri Wijayanti; Fatimah Fatimah (Masyarakat Linguistik Indonesia, 2022)
This paper aims to describe register on Sport Announcer Talk (SAT) in sportfishing ‘Mancing Mania Trans7 Program’. Data were compiled from the document containing register on sportfishing – either vocabulary or syntactic features – which were downloaded from Mancing Mania Trans7 Official channel. Afterwards, data were transcribed ortographically and classified into six domains, namely person, location, activity, technique, equipment, and target fish. Data were analyzed based on the characteristics to determine register by considering vocabulary distinctiveness. Besides that, syntactic aspects were elaborated to show the functional and stylistic features. The result shows that the forms of registers in the field of fishing were dominated by heavy noun modification. English was the dominant language used by the announcer to express the identity of the angler community. There were many metaphorical registers applied for the sake of attractiveness. Finally, the language style is clearly distinguishable from that used in other contexts, especially from other sporting events. The grammar is quite distinctive; it involves features, such as complexity, syntactic reduction and the inversion, heavy noun modification and other stylistic function, such as deictic and exaggerating expressions.